Welcoming the Centenary of the University of Lithuania in Kaunas: Higher Courses, the Beginning of the Development of Academic Surgery, it’s First Heads - Saladžinskas, Žilvinas (Lietuvos chirurgija, 2021)
The origins of higher education in Kaunas began in 1919, during a difficult period for the country, during the struggle for its independence. The young state of Lithuania laid the first foundations of higher education and sought to restore the health care system.The article presents a brief history of the establishment of a higher school in Kaunas, the establishment of higher medical courses and a university. One of the initiators of this work, along with other prominent Lithuanians, was the famous surgeon and public figure at the time Juozas Žemgulys.The emergence of the first departments of surgery at the then University of Lithuania in Kaunas and the beginning of their work is reviewed, the first supervisors Janis Dzirne, Hans Boit, Aleksandr Hagentorn are presented. They significantly contributed to the development of surgery in the country, helped to grow a new generation of Lithuanian surgeons.
Keywords: history of surgery; University of Lithuania in Kaunas; departments of surgery